Anomalous elastic properties across the γ to α volume collapse in cerium. Issue 1 (December 2017) - Lipp, Magnus; Jenei, Zs.; Cynn, H.; Kono, Y.; Park, C.; Kenney-Benson, C.; Evans, W.
Abstract The behavior of thef -electrons in the lanthanides and actinides governs important macroscopic properties but their pressure and temperature dependence is not fully explored. Cerium with nominally just one 4f electron offers a case study with its iso-structural volume collapse from the γ-phase to the α-phase ending in a critical point (p C, V C, T C ), unique among the elements, whose mechanism remains controversial. Here, we present longitudinal (c L ) and transverse sound speeds (c T ) versus pressure from higher than room temperature toT C for the first time. Whilec L experiences a non-linear dip at the volume collapse, c T shows a step-like change. This produces very peculiar macroscopic properties: the minimum in the bulk modulus becomes more pronounced, the step-like increase of the shear modulus diminishes and the Poisson's ratio becomes negative—meaning that cerium becomes auxetic. At the critical point itself cerium lacks any compressive strength but offers resistance to shear. The origin of the volume collapse of cerium, the only elemental metal with a critical point in the solid phase, remains elusive. Here the authors show that, near the critical point, the f-electrons make cerium lose its compressive strength while maintaining a finite shear strength—which makes cerium unexpectedly auxetic.